Changes in the epidemiology and prognosis of Streptococcus pyogenes necrotizing fasciitis after COVID-19: Insights from a university hospital - Guzmán-Sánchez, Álvaro; de la Villa, Sofía; Hernández-Mateo, Jose María; García-Quirós, María Asunción; Benjumea, Antonio; Matas, Jose Antonio; Sánchez-Somolinos, Mar; Vaquero, Javier; Sanz-Ruiz, Pablo (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Following the COVID-19 pandemic, numerous countries have reported a significant increase in invasive Streptococcus pyogenes infections. Our aim was to analyze the epidemiology, clinical characteristics, morbidity, and prognosis of patients with S. pyogenes-associated necrotizing fasciitis in the post-COVID-19 era.Methods: This retrospective study was conducted at a university hospital and included all consecutive adult patients (≥18 years) diagnosed with S. pyogenes-associated necrotizing fasciitis between 2012 and 2023. Two study periods were compared: pre-COVID-19 (2012–2019) and post-COVID-19 (2020–2023). The primary objective was to determine incidence (admissions per 100,000 inhabitants). Secondary outcomes included in-hospital mortality, length of hospital stay and intensive care unit admissions between the periods.Results: A total of 34 cases were included: 17 in the pre-COVID-19 period and 17 in the post-COVID-19 period, with an incidence of 0.42/100,000 vs. 1.13/100,000 inhabitants-year, respectively (P